The Analysis of Semantic Meaning Found in Students’ Interactions in the English Department at Bali Dwipa University - Artini, Ida Ayu Kade Dewi; Suardana, I Putu Eka (UIBU, 2026)
Student communication at the university level involves more than simply sharing information; it also reflects the ways meanings are created and understood. This research explores semantic meaning, focusing on conceptual, connotative, social, affective, and thematic meanings proposed by Leech, as they appear in the interactions of students in the English Department at Bali Dwipa University. The study applies a qualitative descriptive design supported by frequency distribution analysis to examine data drawn from classroom exchanges, group discussions, and informal conversations among peers. The results show that conceptual meaning often appears in academic clarifications, while connotative meaning is visible in implied or figurative expressions. Social meaning can be seen in the use of politeness and honorific forms, while affective meaning expresses students’ feelings such as motivation, doubt, or humor. Thematic meaning arises from the way students organize sentences to highlight particular ideas. The frequency distribution further indicates the relative occurrence of each semantic meaning across the collected interactions. These findings suggest that student interactions are rich in semantic features that demonstrate both their language ability and social relationships. The research concludes that awareness of semantic aspects can support more effective teaching and communication in higher education.